2013
DOI: 10.1177/1087057112463066
|View full text |Cite
|
Sign up to set email alerts
|

Creation of a Six-fingered Artificial Transcription Factor That Represses the Hepatitis B Virus HBx Gene Integrated into a Human Hepatocellular Carcinoma Cell Line

Abstract: Chronic hepatitis B virus (HBV) infection is an independent risk factor for the development of hepatocellular carcinoma (HCC). The HBV HBx gene is frequently identified as an integrant in the chromosomal DNA of patients with HCC. HBx encodes the X protein (HBx), a putative viral oncoprotein that affects transcriptional regulation of several cellular genes. Therefore, HBx may be an ideal target to impede the progression of HBV infection-related HCC. In this study, integrated HBx was transcriptionally downregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Zinc finger nucleases have successfully been used in tissue culture to reduce HBV levels . For example Weber et al developed a zinc finger nuclease that targeted the core and pol regions of cccDNA.…”
Section: Novel Therapeutic Strategies In Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc finger nucleases have successfully been used in tissue culture to reduce HBV levels . For example Weber et al developed a zinc finger nuclease that targeted the core and pol regions of cccDNA.…”
Section: Novel Therapeutic Strategies In Developmentmentioning
confidence: 99%
“…43 Zinc finger nucleases have successfully been used in tissue culture to reduce HBV levels. [44][45][46][47] For example Weber et al developed a zinc finger nuclease that targeted the core and pol regions of cccDNA. Using an adeno-associated virus (AAV) delivery system, they showed that HBV production from HepAD38 cells could be significantly controlled upon zinc finger nuclease delivery.…”
Section: Gene-editing Strategiesmentioning
confidence: 99%
“…In this regard, Hepadnaviruses, which do not carry any integration machinery so their integration is dependent on double‐strand breaks, act along with the cell repair machinery to integrate viral genomes in fragile sites of the host cell genome . In order to overcome these possible off‐targeting effect and the likely increase of potentially disturbing integration events, new approaches using obligate heterodimeric nucleases coupled to two different targeting domains and the targeting of non‐nuclease effector domains, like epigenetic modulators (DNMTs, histone modifiers) or transcription downregulators (KRAB) are of considerable interest.…”
Section: Future Hepatitis B Treatment Optionsmentioning
confidence: 99%
“…Zhao et al, 26 investigated the use of a ZFP-based artificial transcription factor (ATF) to inhibit function of the enhancer I region and diminish X expression. Two three-fingered ZFP motifs were linked to form a six-fingered DNA binding domain that recognized an 18 base pair sequence.…”
Section: Engineering Zfps To Disable Hbv Replicationmentioning
confidence: 99%